Five nights at Freddy's. Fazbear frights : graphic novel collection. Vol. 2 - Cawthon, Scott, 1971-; Waggener, Andrea Rains, 1960-; West, Carly Anne; Hastings, Chris, 1983- (Graphix, an imprint of Scholastic, 2023)
"Oscar, ever the miniature grown-up his mom needs him to be, decides to take something he wants . . . even though he knows it's wrong. Stanley is newly dumped, stuck in a dead-end job for a mysterious employer, and unable to connect with anyone. And Devon, abandoned by his dad and ignored by his mom, can't understand why love and friendship come so easily to everyone except him. Unfortunately, in the callous world of Five Nights at Freddy's, it's always in the depths of loneliness when evil creeps in. In this volume, three stories from the New York Times bestselling series Five Nights at Freddy's: Fazbear Frights come to life in delightfully horrifying comics. Readers beware: This collection of terrifying tales is enough to unsettle even the most hardened Five Nights at Freddy's fans."--Back cover.